Case Study : Smiling Orchid Bakery & Cake / Mohamed Zuheel Zaid - Zaid, Mohamed Zuheel (2020)
Smiling Orchid Bakery & Cake is located at 473, Jalan Dato Nik Mustapha, 17500 Tanah Merah Kelantan. This bakery was established on year 1992 and was running the business for about 28 years. Besides, Smiling Orchid Bakery & Cake owned a factory that is located at Lot 6750 Jalan Jedok 17500, Tanah Merah Kelantan. This factory was built to process the products such as bake the cakes and breads. Then, the processed products will be sent to the bakery. All the decorations of the cakes and breads will be done here and the finished products then will be sold to the customers. Smiling Orchid also has another two businesses which are Smiling Orchid Ingredients Trading and Smiling Orchid Coffee. Smiling Orchid Ingredients Trading has two branches that are located at 3243, 3244 Jalan Jedok 17500, Tanah Merah Kelantan and PT 242 Jalan Masjid Lama 17000, Pasir Mas Kelantan. This business supplies the raw ingredients and tools for making cakes and desserts such as flour, sugar and margarine. Another business is Smiling Orchid Coffee that is located at B 616, Jalan Jedok 17500, Tanah Merah Kelantan. This cafe provides many kinds of beverages, western foods, desserts and side dishes. The customers can enjoy the delicious menu at the café